2018
DOI: 10.1016/j.ymthe.2018.02.024
|View full text |Cite
|
Sign up to set email alerts
|

A Positive Feed-Forward Loop between LncRNA-CYTOR and Wnt/β-Catenin Signaling Promotes Metastasis of Colon Cancer

Abstract: We previously demonstrated that long non-coding RNA cytoskeleton regulator RNA (CYTOR), also known as Linc00152, was significantly overexpressed in colon cancer and conferred resistance to oxaliplatin-induced apoptosis. At the same time, elevated CYTOR expression was also reported in gastric cancer and exerted influences on epithelial-mesenchymal transition (EMT) markers. However, the precise mechanism by which CYTOR promotes the EMT phenotype and cancer metastasis remains poorly understood. Here, we showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
147
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(151 citation statements)
references
References 47 publications
3
147
1
Order By: Relevance
“…In colorectal cancer, linc00152 promotes the proliferation, migration, and invasion in the miR‐139‐5p/NOTCH 1 axis, while also inducing the resistance of colorectal cancer cells to 5‐fluorouracil‐mediated apoptosis . Moreover, linc00152 can facilitate the epithelial‐to‐mesenchymal transition and metastasis in colon cancer by binding to cytoplasmic β‐catenin, thereby impeding casein kinase 1 (CK1)‐induced β‐catenin phosphorylation and enabling β‐catenin as well as linc00152 to be translocated into the nucleus in a positive feed‐forward circuit …”
Section: Molecular Functions and Mechanisms Of Linc00152 In Human Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In colorectal cancer, linc00152 promotes the proliferation, migration, and invasion in the miR‐139‐5p/NOTCH 1 axis, while also inducing the resistance of colorectal cancer cells to 5‐fluorouracil‐mediated apoptosis . Moreover, linc00152 can facilitate the epithelial‐to‐mesenchymal transition and metastasis in colon cancer by binding to cytoplasmic β‐catenin, thereby impeding casein kinase 1 (CK1)‐induced β‐catenin phosphorylation and enabling β‐catenin as well as linc00152 to be translocated into the nucleus in a positive feed‐forward circuit …”
Section: Molecular Functions and Mechanisms Of Linc00152 In Human Tumorsmentioning
confidence: 99%
“…50,51 Moreover, linc00152 can facilitate the epithelial-to-mesenchymal transition and metastasis in colon cancer by binding to cytoplasmic β-catenin, thereby impeding casein kinase 1 (CK1)-induced β-catenin phosphorylation and enabling β-catenin as well as linc00152 to be translocated into the nucleus in a positive feed-forward circuit. 52 The progression of renal cell carcinoma is correlated with the elevated level of linc00152, which contributes to lymph node metastases, advances in TNM stage, and shorter overall survival. Additionally, downregulated linc00152 expression decreases cell proliferation and shortens the S phase, possibly because of the epigenetic suppression of P16 and inhibition of miR-205.…”
Section: Overexpression Of Linc00152 Enhances Cell Proliferation Imentioning
confidence: 99%
“…As far as we know, this study was the first assessment of clinical value of CYTOR expression in CRC patients based on the large sample investigation and data analysis. The poor prognosis may be due to the high-CYTOR expression that promoted proliferation and metastasis in CRC cells as previously reported (Yue et al, 2018). Meanwhile, resistance to antitumor drugs may be another reason for poor…”
Section: Discussionmentioning
confidence: 52%
“…CYTOR is also called LINC00152, previous studies showed that the expression of lncRNA CYTOR was up-regulated in multiple malignant diseases, such as gastrointestinal cancer, liver cancer, lung adenocarcinoma and esophageal squamous cell carcinoma [25][26][27][28]. Yue et al [29] showed that CYTOR promoted metastasis of colon cancer through Wnt/β-catenin signal pathway. Reon et al [30] reported that CYTOR promoted invasion via a 3'-hairpin structure, and as a effective biomarker for predicting survival of glioblastoma.…”
Section: Functional Prediction Of Three Lncrnasmentioning
confidence: 99%